Property rights with price tags? Pricing uncertainties in the production, transaction and consumption of China's small property right housing. (February 2019) - He, Shenjing; Wang, Dong; Webster, Chris; Chau, Kwong Wing
Abstract: The booming informal housing market has played an important role in providing inexpensive housing for lower income population in the developing world. In China, an informal housing strategy known as "Small Property Right Housing (SPRH)" is thriving on collective land owned by village collectives, and providing housing for more than a quarter of a billion people. Why and how the informal housing market has emerged and operates have been widely explored theoretically and empirically from the perspective of the peculiar arrangement of property rights that has created this market. Yet, we know very little about the pricing of this market, with its various constraints and uncertainties associated with the incomplete property rights. Most existing research takes a standard dichotomous view of property rights and thus overlooks the complexity of the degrees of rights that make possible this thriving informal market. Our study takes the more heterodox idea of a bundle of property rights that taken as a whole confers a graded degree of protection to a buyer at production, transaction and consumption stage, to understand offer-price determination in the SPRH market of China. Drawing on a large database of SPRH records in the city of Shenzhen, this is among the first attempts to quantitatively examine the pricing mechanism of China's informal housing market. Our results show that even without clearly defined property rights, a well-functioning market of SPRH can exist. We find that the ambiguous rights created by the informal institutions involved in the production, transaction and consumption of SPRH are capitalised in the price. This research is of theoretical and empirical significance to understand the dynamics of informal housing development and how the market behaves when property rights are ill-defined.